The Effect of Capital Structure, Sales Growth and Company Size on Financial Stability in Food & Beverage Subsector Companies Listed on The Idx for the 2022-2024 Period - Natasya, Putri; Anita, Nur (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
This study aims to analyze the effect of capital structure, sales growth, and firm size on financial stability in food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The study employs a quantitative approach using secondary data from audited financial statements of 34 companies, resulting in 102 observations selected through purposive sampling. Capital structure is proxied by the Debt to Equity Ratio (DER), sales growth is measured by the percentage change in net sales, firm size is measured using the natural logarithm of total assets, and financial stability is measured using the Current Ratio (CR). The data are analyzed using multiple linear regression. The results indicate that capital structure has no significant effect on financial stability, while sales growth and firm size have a positive and significant effect. Furthermore, the simultaneous test shows that capital structure, sales growth, and firm size jointly have a significant effect on financial stability. From a theoretical perspective, this study provides empirical evidence that internal growth factors and firm scale play a more dominant role in maintaining financial stability than capital structure in the food and beverage subsector. From a practical perspective, the findings offer insights for managers and investors to focus on sustainable sales growth and optimal asset management to strengthen firms’ financial stability.